Capitalism Work Problems: An Analysis Study of Islamic Worldview - Adryan Risady; Khoirul Umam (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Work can have a negative impact on a person's life. We can see this from the emergence of work cultures such as karoshi. So it is not surprising that many cases of suicide are found due to excessive work. Apart from that, quite a few successful people whose lives ended tragically, such as Marilyn Monroe, who died after consuming illegal drugs. In fact, they should live happily and peacefully. This shows that the success of a person's career does not guarantee happiness in his life. Islam does not deny working as an individual interest, but it is also related to social interests. This is certainly different from the working concept of Capitalism. This article aims to examine how the concept works in Islam, as well as providing a critique of the working concept of Capitalism. The contribution of this research is to provide a deeper understanding of how Islamic values ​​can offer a more balanced and sustainable alternative in the world of work compared to the capitalist paradigm which often prioritizes personal profit above individual and social welfare. By comparing these two concepts, this research seeks to provide a more holistic insight into how healthy ways of working can be achieved and implemented in modern society.